2013
DOI: 10.1080/00103624.2012.748008
|View full text |Cite
|
Sign up to set email alerts
|

Groundcover as a Useful Tool for Efficient Resource Management and Sustainable Production

Abstract: A field trial has been conducted on 5-year-old Sweet Lady and Royal Glory peach cultivars on a sandy loam soil at Siófok, West Hungary, since 2009. Four in-row ground management systems (pine bark mulch, cow manure, black fabric cover, and no cover with herbicide applications) were evaluated in a plot design with three replicates to study their effects on the soil temperature and nutrient contents of leaves. The fluctuation of soil temperature was more moderate with mulch and manure as groundcover. Leaf nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…The inorganic form of GC includes white transparent film, black plastic film, biodegradable plastic film, and water‐permeable plastic film (Li et al, 2012). Organic forms of GC reduce soil temperature fluctuations (Nagy et al, 2013) while increasing soil total nitrogen, microbial biomass, and soil available nitrogen (Nikiema et al, 2012). The use of organic GC, in combination with other orchard management practices, reduces pest pressure in peach orchards thereby reducing reliance on conventional pesticides while increasing fruit size, yield, and quality (Bussi et al, 2016; Johnson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The inorganic form of GC includes white transparent film, black plastic film, biodegradable plastic film, and water‐permeable plastic film (Li et al, 2012). Organic forms of GC reduce soil temperature fluctuations (Nagy et al, 2013) while increasing soil total nitrogen, microbial biomass, and soil available nitrogen (Nikiema et al, 2012). The use of organic GC, in combination with other orchard management practices, reduces pest pressure in peach orchards thereby reducing reliance on conventional pesticides while increasing fruit size, yield, and quality (Bussi et al, 2016; Johnson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Leaf and fruit nitrogen levels were normal in both the organic and integrated production treatments (Wooldridge, 2013). Nagy et al(2013) laid out a field trial on five-year-old Sweet Lady and Royal Glory peach cultivars on a sandy loam soil. Four in-row ground management systems were evaluated and they observed that leaf nitrogen, potassium and calcium concentrations increased with mulch but leaf magnesium and zinc decreased with the orchard floor management treatments.…”
Section: Effect Of Orchard Floor Management Practices On Leaf and Fruit Nutrient Statusmentioning
confidence: 99%